From genes to ecosystems: A multidisciplinary approach to understanding and conservation challenges for the short-tailed sea snake Hydrophis curtus (Shaw, 1802) in India - Prachi Hatkar; Satyam Gupta; Chinnasamy Ramesh (Universitas Malikussaleh, 2025)
The reduction of marine reptile populations has emerged as a worldwide issue, prompting comprehensive investigations into the effects of altering environmental conditions. Examining sea snakes has consistently posed difficulties owing to the complexities of collecting, maintaining, and researching them in natural and controlled environments. The Hydrophiinae family of venomous marine snakes encompasses the Spine-bellied or Short-tailed sea snake, Hydrophis curtus, which is distributed from the Persian Gulf to eastern Australia. This study examines the conservation problems of H. curtus, incorporating genetic, ecological, and environmental methodologies to evaluate its population status and risks thoroughly. We thoroughly analysed 123 scientific publications published between 1802 and 2024, examining many facets of sea snake biology and the risks they encounter. This review consolidates and synthesizes prior research on H. curtus, emphasizing its interactions with humans in coastal India and adjacent areas. The review encompassed several subjects, including species distribution, habitat utilization, feeding ecology, reproductive behaviour, venom characteristics, and conservation challenges. Through field surveys, genomic methodologies, and habitat modelling, we ascertain critical conservation priorities and recommend management methods. Our results demonstrate considerable genetic diversity, substantial habitat concerns, and mortality imposed by fishing. The research emphasizes the necessity for focused conservation measures, encompassing habitat preservation, policy integration, and sustainable fisheries management.